Giant Polarization Sustainability in Ultrathin Ferroelectric Films Stabilized by Charge Transfer. Issue 46 (25th October 2017) - Zhang, Sirui; Zhu, Yinlian; Tang, Yunlong; Liu, Ying; Li, Shuang; Han, Mengjiao; Ma, Jinyuan; Wu, Bo; Chen, Zuhuang; Saremi, Sahar; Ma, Xiuliang
Abstract: Ferroelectricity is generally deteriorated or even vanishes when the ferroelectric films are downsized to unit cell scale. To maintain and enhance the polarization in nanoscale ferroelectrics are of scientific and technological importance. Here, giant polarization sustainability is reported in a series of ultrathin PbTiO3 films scaled down to three unit cells grown on NdGaO3 (110) substrates with La0.7 Sr0.3 MnO3 as bottom electrodes. Atomic mappings via aberration‐corrected scanning transmission electron microscopy demonstrate the robust ferroelectricity for the sub‐10 nm thick film. For the 1.2 nm thick film, the polarization reaches ≈50 µC cm −2 . The 2 nm thick film possesses a polarization as high as the bulk value. The films ranging from 10 to 35 nm display a giant elongation of out‐of‐plane lattice parameter, which corresponds to a polarization of 100 µC cm −2, 20% larger than that of the bulk PbTiO3 . The giant enhancement of polarization in the present films is proposed to result from the charge transfer at the La0.7 Sr0.3 MnO3 /PbTiO3 interface, as supported by the anomalous decrease of Mn valence measured from X‐ray photoelectron spectroscopy. These results reveal the significant role of charge transfer at interfaces in improving large polarizations in ultrathin ferroelectrics and are meaningful for the development of future electronic devices. Abstract : A series of ultrathin PbTiO3 films is grown on La0.7 Sr0.3 MnO3 ‐buffered NdGaO3 (110) substrates. C s‐corrected scanning transmission electron microscopy demonstrates the ferroelectricity for the 1.2 nm thick film with the polarization of ≈50 µC cm −2 . The 2 nm thick film possesses a polarization of bulk value. The giant enhancement of polarization is proposed to result from the charge transfer at interfaces.